Correction of supraventricular tachicardia in children of first year of age - Meshkova, M.; Doronin, O.; Khanenova, V.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2016)
In this article we analyzed our own experience of the treatment of supraventricular tachycardia in children of the first year of life. The studied group included 114 patients, who were treated in Ukrainian Children’s Cardiac Center from 2009 to 2015 years. All patients in the first stage underwent antiarrhythmic drugs selection. Selected effective therapy was discontinued at the age of 1 year with a further rhythm assessment. In 4 children with ineffective antiarrhythmic therapy were performed radiofrequency catheter ablations of the arrhythmia substrate. No complications of treatment were observed.